Interpersonal Cognitive Distortions: What is the Role of Childhood Trauma and Attachment? - Meva Demir-Kaya; Feridun Kaya; Yüksel Eroğlu (Journal of Education in Science, Environment and Health)
The aim of this study is to investigate the mediating role of attachment styles in the relationship between childhood trauma and cognitive distortion. The sample comprised 358 (44.7 % males) university students. Participants completed the Childhood Trauma Questionnaire, the Three-Dimensional Attachment Style Scale, and the Interpersonal Cognitive Distortions Scale. According to the results, other variables, except for physical neglect, did not differ in terms of gender. According to other results of the research, childhood trauma and anxious attachment predicted interpersonal cognitive distortions. In addition, anxious attachment mediated the relationship between childhood trauma and interpersonal cognitive distortions. These findings provide evidence that childhood trauma, mediated by anxious attachment, might contribute to interpersonal cognitive distortions in adulthood. However, secure and avoidant attachment had no statistically meaningful direct impact on interpersonal cognitive distortions. Findings were discussed in line with the relevant literature and some suggestions were presented to the researchers in the context of planning treatment, including assessment of prognosis and treatment needs.